Use the quadratic formula to solve. Express your answer in simplest form. \[ 4 k^{2}+6 k+1=2 k \]
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
First, let's rearrange the equation to standard quadratic form. We start with: \[ 4k^2 + 6k + 1 = 2k \] Subtracting \(2k\) from both sides, we get: \[ 4k^2 + 6k - 2k + 1 = 0 \] This simplifies to: \[ 4k^2 + 4k + 1 = 0 \] Now, we can apply the quadratic formula, which is: \[ k = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] In our equation, \(a = 4\), \(b = 4\), and \(c = 1\). Plugging the values into the formula: \[ b^2 - 4ac = 4^2 - 4(4)(1) = 16 - 16 = 0 \] Since the discriminant is \(0\), there will be one real solution. Now, substituting back into the quadratic formula: \[ k = \frac{-4 \pm \sqrt{0}}{2(4)} = \frac{-4 \pm 0}{8} = \frac{-4}{8} = -\frac{1}{2} \] So the solution to the equation is: \[ k = -\frac{1}{2} \]